THE NATURE OF CORPORATE RESIDUAL EQUITY UNDER THE ENTITY CONCEPT. - Li, David H. (The Accounting Review, 1960)
Abstract Under the entity concept, the corporation is an institution in its own right and a competent party to contract. In contracting for capital supplied by stockholders, the only significant representation made by the corporation is for it to agree to pay dividends when and if declared. From this, it is deduced that, in a stock issue, the offering price constitutes consideration for the right to receive future dividends. Furthermore, it is argued that stockholders do not have a claim to capital thus supplied so long as the corporation remains a going concern, an implicit assumption of the entity concept. From these, it is concluded that capital supplied by stockholders becomes the equity of the corporation. It is also argued that the acceptance of this view will not retard the stockholders' supplying capital to the corporation and that the payment of dividends is consistent with the corporation's striving to survive and to maintain an attractive investment atmosphere. On the contrary, the acceptance of this view tends to remove an area of inconsistency related to the treatment of retained earnings under the entity concept.